2007
DOI: 10.1016/j.tmrv.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen and Diphenhydramine Premedication for Allergic and Febrile Nonhemolytic Transfusion Reactions: Good Prophylaxis or Bad Practice?

Abstract: Febrile non-hemolytic and allergic reactions are the most common transfusion reactions, but usually do not cause significant morbidity. In an attempt to prevent these reactions, US physicians prescribe acetaminophen or diphenhydramine premedication before more than 50% of blood component transfusions. Acetaminophen and diphenhydramine are effective therapies for fever and allergy respectively, so their use in transfusion has some biologic rationale. However, these medications also have potential toxicity, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
2
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 63 publications
6
120
2
6
Order By: Relevance
“…Although reports revealed that allergic reactions with platelets (PLTs) and red blood cells (RBCs) have an incidence rate of 3Á7% and 0Á15%, respectively, a review of the literature showed that the incidence rate varied by more than 100-fold, probably because of differences in pre-medication use, patient characteristics, product manufacturing, storage time, reporting rates, reaction definitions and monitoring standards (Geiger & Howard, 2007). A Canadian group showed similar allergic reaction incidences with PLTs and RBCs and an allergic reaction incidence of 0Á19% with plasma transfusions (Kleinman et al, 2003).…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Although reports revealed that allergic reactions with platelets (PLTs) and red blood cells (RBCs) have an incidence rate of 3Á7% and 0Á15%, respectively, a review of the literature showed that the incidence rate varied by more than 100-fold, probably because of differences in pre-medication use, patient characteristics, product manufacturing, storage time, reporting rates, reaction definitions and monitoring standards (Geiger & Howard, 2007). A Canadian group showed similar allergic reaction incidences with PLTs and RBCs and an allergic reaction incidence of 0Á19% with plasma transfusions (Kleinman et al, 2003).…”
Section: Incidencementioning
confidence: 99%
“…Although pre-transfusion medications are not effective, most transfusion reactions are easily treated (Geiger & Howard, 2007;Roback et al, 2011). When urticaria occurs, diphenhydramine may be administered.…”
Section: Treatmentmentioning
confidence: 99%
“…Other more specific causes require more specific approach in conjunction with antipyretic therapy, for instance, corticosteroids and antihistamine for allergic drug reactions [78], dantrolene sodium in malignant hyperthermia [65][66][67], antiepileptic drugs and benzodiazepines in epilepsy with febrile seizures [79] and anticoagulant prophylaxis for deep vein thrombosis [80]. In depth discussions of such conditions are however, beyond the scope of this article.…”
Section: Managementmentioning
confidence: 99%
“…Three kinds of drugs are commonly used for this pre-transfusion medication, either alone or in combination (Patterson et al, 2000). United States Physicians use acetaminophen and diphenhydramine as effective therapies for fever and allergy, respectively (Geiger and Howard, 2007). Diphenhydramine is a first-generation antihistamine drug used for treating allergic transfusion reaction and causes drowsiness, affecting alertness, and impairing cognitive performance (Banerji et al, 2007).…”
Section: Introductionmentioning
confidence: 99%